A Climate – Responsive Conceptual Framework for Assessing Water Ecological Carrying Capacity in Urban Watershed - Minarti, Astari; Rinanti, Astri; Fachrul, Melati Ferianita; Hendrawan, Diana Irvindiaty; Septiani, Winnie (Fakultas Teknik, Universitas Pasundan, 2025)
Rapid urbanization and climate variability have degraded water quality and reduced the resilience of urban watershed. This study proposes a climate-responsive conceptual framework for assessing Water Ecological Carrying Capacity (WECC) in urban environments. The framework integrates hydro – climatic indicators, urban – climatic dynamics, and adaptive policy interventions, structured within the Driver–Pressure–State–Impact–Response (DPSIR) model. It is designed to evaluate the dynamic interactions between urban growth, climate variability, and freshwater ecosystem thresholds. A systematic review of 14 studies from Asia and beyond provides empirical support for the framework. Indicators such as streamflow variability, urban land use, water temperature, and governance capacity are categorized within the DPSIR components to illustrate the multifaceted nature of WECC. The study highlights how hydro – climatic and socio – economic stressors interact to influence the vulnerability and resilience of water ecosystems. Figures and tables within the paper visualize these interactions and simulate feedback loops under various environmental and policy scenarios. While the model presents a comprehensive and adaptable framework, it is based on secondary data and lacks validation through localized, real-time application. Nevertheless, it serves as a strategic tool for anticipating and addressing urban water sustainability challenges. It encourages the use of integrated, climate – informed planning approaches and provides a foundation for future research and policy in climate – sensitive regions. This study underscores the importance of evaluating WECC not as a static measure but as a dynamic function shaped by ecological, social, and climatic processes.